Oral Suspension as Versatile Galenic Formulation in Pediatry - Luisetto, Mauro; N, Almukthar; K, Edbey; GR, Mashori; C, Fiazza; l, Dona’; L, Cabianca; O, Latyshev (Archives of Pharmacy and Pharmaceutical Sciences, 2024)
In the last years, there has been an increase in the prescription of drugs in pediatry as a pharmaceutical form of oral suspension. The same is true in commerce there are various producers that provide specific ready-for-use excipients to make more easier to prepare OS in the galenic laboratory. The aim of this work is to verify the advantages of this pharmaceutical form to cover pediatric dosages vs. other forms and also to overcome shortcomings of some crucial registered drugs. In this work scientific literature is reported that also relates to some ready-for-use products as bases-vehicle for suspension and some formulations of interest.